Development of a novel Guinea Pig model producing transgenerational endothelial transcriptional changes driven by maternal food restriction and a second metabolic insult of high fat diet - Le, Hillary H.; Hagen, Matthew W.; Louey, Samantha; Tavori, Hagai; Thornburg, Kent L.; Giraud, George D.; Hinds, Monica T.; Barnes, Anthony P. (Frontiers in Physiology, 2023)
Developmental programming of chronic adverse cardiovascular health outcomes has been studied both using numerous human populations and an array of animal models. However, the mechanisms that produce transgenerational effects have been difficult to study due to a lack of developmentally relevant models. As such, how increased disease risk is carried to the second generation has been poorly studied. We hypothesized that the endothelium which mediates many acute and chronic vascular inflammatory responses is a key player in these effects, and epidemiological studies implicate transgenerational nutritional effects on endothelial health. To study the mutigenerational effects of maternal undernutrition on offspring endothelial health, we developed a model of transgenerational nutritional stress in guinea pigs, a translationally relevant precocial species with a relatively short lifespan. First-and second-generation offspring were subjected to a high fat diet in adolescence to exacerbate negative cardiovascular health. To assess transcriptional changes, we performed bulk RNA-sequencing in carotid artery endothelial cells, with groups stratified as prenatal control or food restricted, and postnatal control or high fat diet. We detected statistically significant gene alterations for each dietary permutation, some of which were unique to treatments and other transcriptional signatures shared by multiple or all conditions. These findings highlight a core group of genes altered by high fat diet that is shared by all cohorts and a divergence of transgenerational effects between the prenatal ad libitum and dietary restriction groups. This study establishes the groundwork for this model to be used to better understand the interplay of prenatal stress and genetic reprogramming.